MERIAM KUNO KIARACONDONG, BANDUNG - Abrianto, Octaviadi (PANALUNGTIK, 2018)
European colonialism in Asia and Africa was so successful mainly because of their weaponry were more superior than their opponent, one of these weapon is the cannon. One of these cannon was found in Kiaracondong area in Bandung, which raise the question about its shape, material and when its cast. Inductive method was used to answer thesequestions. The cannon wasa19th century bronze cannon cast in de Hague by J. J. Maritz and by its attributes was use as ship cannon.